Tinjauan Ketidaklengkapan Pengisian Resume Medis Pasien Rawat Inap di RS Setia Mitra Tahun 2018 - Diaz Maulana; Hudiyati Agustini (APIKES Bhumi Husada Jakarta, 2018)
ABSTRAK Based on preliminary observations carried out the medical records of the Setia Mitra Hospital in March 2018 of the 10 medical resumes observed were incomplete results with an average proportion of 14%. The purpose of this study was to find out the description of the incompleteness of filling out medical resumes of hospitalized patients at Setia Mitra Hospital. Specific Objectives, namely (1) identifying Standard Operating Procedures (SOP) filling in medical resumes of hospitalized patients. (2) identify the contents of the inpatient medical resume form. (3) calculate the number of incompleteness in filling out medical resumes of inpatients. The method used is descriptive method. Based on the results of research on 169 medical resume forms conducted at Setia Mitra Hospital, the authors can draw conclusions that the Setia Mitra Hospital has Standard Operating Procedures (SOP). There is a difference in the application of the part of the medical resume form in Setia Mitra Hospital, the application of which differs from the Standard Operating Procedure (SOP) that is established and also according to the provisions of the Komisi Akreditasi Rumah Sakit (KARS). The results of calculations according to quantitative analysis with a sample of 169 medical resumes from 293 medical resumes as a result of completing the medical resume form of incomplete inpatients 100% only reached the completeness value of 12% with an incomplete value of 88%. The author's suggestion is to evaluate the medical resume form so that it is in accordance with the provisions of the Komisi Akreditasi Rumah Sakit (KARS) so that the parts that must be filled are simpler, easier to fill and can be completed. Need to be re-socialized to medical personnel to fill out completely. If there is a section that cannot be completed, it is filled with the phrase